Applying domain knowledge and academic information to enhance unknown-item search in OPAC - Intarapaiboon, Peerasak; Kesamoon, Chainarong (Malaysian Journal of Library and Information Science, 2019)
Many students usually use the unknown-item search strategies, including subject and keyword searches, to retrieve books or other materials provided in library catalogs. However, the success rates for unknown-item searching is relatively low compared with the known-item search strategies, i.e., title or author searches. In this paper, a framework for improving the unknown-item search is proposed. The main contributions of our framework concern both user's keywords and book indexing: (i) To enhance a user's keyword, the framework will select other relevant terms in a domain-related ontology; (ii) Topics expressed in course description are used as book indexing. A preliminary experiment shows that the proposed framework gives satisfactory results in terms of the numbers and the precision scores of retrieved books. Furthermore, the proposed interesting-score measure can facilitate to lift the precision levels.